Understanding the Prevalence of Nomophobia: A Perspective of University Students - Iram Naz; Tamkeen Fatima; Sameera Shafiq; Shumaila Ilyas (Journal for Social Science Archives, 2025)
This cross-sectional study examined the prevalence of nomophobia among students at the University of Gujrat Pakistan. Nomophobia, which is "the fear of being unable to use or be without one’s mobile device," is a major mental health concern in the current digital age, especially for university students who are heavy mobile device users. A non-probability convenience sample of 700 university students (ages 18-25, smartphone users) participated in the study and data were collected through a demographic form and the Nomophobia Questionnaire (NMP-Q). NMP-Q scores were analyzed with descriptive statistics and percentiles to examine prevalence levels (low, moderate, high/severe). The findings revealed a high prevalence of nomophobia in the student sample, with 75% of participants experiencing some level of nomophobia. The findings indicate that, specifically, 24.71% of students had low nomophobia, 50.29% of students had moderate nomophobia, and 25.00% of students had high/severe nomophobia. The total moderate to high prevalence of nomophobia (75%) is strongly corroborated by international empirical studies, which highlight it as a major public health problem among college students. The study showed that female, younger (ages 18-21), undergraduates (BS), and students who use an Android device and/or use multiple social media sites were the majority sample of prevalence of nomophobia. These results suggest possible connections to socio-emotional communication challenges, life transition, socio-economic status, and fear of missing out (FoMO).